Sleep and dreaming in patients with borderline personality disorder: A polysomnographic study - Schredl, Michael; Schmahl, Christian; Bohus, Martin (Psychiatry research, 2012)
Previous research has demonstrated disturbances in sleep continuity in subjects with borderline personality disorders (BPD). Moreover, depression-like sleep abnormalities like reduced REM latency have been found in BPD subjects, even without comorbid major depression disorder. Yet it is still unknown what the effect is of co-morbid posttraumatic stress disorder on sleep continuity and dream content in BPD patients group. The present study compared 27 unmedicated female BPD subjects and healthy controls. The patients exhibited increased sleep fragmentation, increased REM density, and reduced REM latency. The findings were independent from co-morbid posttraumatic stress response (PTSD), which was present in 33% of the patient sample. Negatively toned dreams obtained by REM awakenings and nightmares were also reported more often by the patients—also irrespective of co-morbid PTSD—whereas dreams of specific BPD behavior, like self-mutilation, were rare. Taking these finding into account, one might productively investigate whether the sleep abnormalities improve during successful treatment of BPD and whether efficient methods for treating nightmares can be beneficial for this patient group.